Partial AVSD with cortriatriatum sinister with unroofed coronary sinus in an adult - Amitabh Satsangi; Sheikh Mohd Murtaza (Annals of Pediatric Cardiology)
Atrioventricular septal defect (AVSD) with cor triatriatum sinister (CTS) is a rare congenital anomalous combination. Few cases of AVSD and CTS have been reported in the literature. However, an isolated case of CTS with partial AVSD, left superior vena cava, and unroofed coronary sinus in an adult has not been reported in the literature. A 20-year-old male, a known case of partial AVSD with CTS, presented with dyspnea on exertion. The patient was surgically managed after a thorough preoperative evaluation and had an uneventful postoperative course. Meticulous evaluation with multiple imaging in the preoperative workup is required in all cases of AVSD to look for associated lesions.